2022
DOI: 10.1002/jbm.b.35209
|View full text |Cite
|
Sign up to set email alerts
|

Release of drugs used in the treatment of osteoporosis from zeolites with divalent ions—Influence of the type of ion and drug on the release profile

Abstract: Bisphosphonates are drugs that are used to treat osteoporosis that causes the low mineral density of the bones. These drugs can be delivered in several ways, but each method has disadvantages. Materials with high potential as carriers of these drugs are zeolites with divalent ions. The aim of this study was to investigate the effect of divalent cations (calcium, magnesium, zinc) and drug type (risedronate, zoledronate) on sorption and release of the drug for osteoporosis. It was proved that drug sorption occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Moreover, it can be seen that the ion exchange does not affect the agglomeration of the particles, which could eliminate them as potential drug carriers. 34 , 35 In the case of SEM images after the epigallocatechin gallate sorption process, the zeolites do not differ significantly from their images before drug attachment. The particles are typical of a microporous aluminosilicate structure with regularly occurring crystals.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, it can be seen that the ion exchange does not affect the agglomeration of the particles, which could eliminate them as potential drug carriers. 34 , 35 In the case of SEM images after the epigallocatechin gallate sorption process, the zeolites do not differ significantly from their images before drug attachment. The particles are typical of a microporous aluminosilicate structure with regularly occurring crystals.…”
Section: Resultsmentioning
confidence: 95%
“…This means that the inclusion of magnesium, calcium, strontium, and zinc ions does not change the appearance and size of the zeolite particles, and the elements did not deposit on the surface of the materials in the form of chlorides or oxides. Moreover, it can be seen that the ion exchange does not affect the agglomeration of the particles, which could eliminate them as potential drug carriers. , In the case of SEM images after the epigallocatechin gallate sorption process, the zeolites do not differ significantly from their images before drug attachment. The particles are typical of a microporous aluminosilicate structure with regularly occurring crystals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when we look at the % release relative to the amount of drug retained, the magnesium material releases more drug. This is due to the fact that zinc ions better complex the drug and retain it longer in the zeolite layer [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to their structural properties, biocompatibility, and stability in biological environments, these porous materials have numerous applications in biology as an active ingredient as well as a drug carrier. It is observed that when both the zeolite and a drug are administered simultaneously to a patient, the pharmacological effect of the drug is not lost. It has been shown that the encapsulation of some hydrophobic chemotherapeutic medicines such as 5-fluorouracil, temozolomide, and α-cyano-4-hydroxy-cinnamic acid in various zeolite structures enhanced the action of drug molecules in biological system. ,, Even the internalization of various zeolite moieties within cancer cells was found to be faster than the normal cell lines. Encapsulation of different transition-metal complexes with molecular dimensions comparable to the diameter of zeolitic cavities has been immensely endeavored and numerous applications have been accentuated. A copper Schiff base complex encapsulated inside zeolite-Y was screened for its cytotoxic activity. Interestingly, in comparison to cisplatin, a zeolite-Y-encapsulated Cu­(II)­hydrazone complex has shown a superior therapeutic effect in HePG2 cells (human liver cancer).…”
Section: Introductionmentioning
confidence: 99%